Peta Dakwah di Kecamatan Tigo Lurah Kabupaten Solok - Afrizal Afrizal; Penmardianto Penmardianto (Lembaga Yasin AlSys, 2026)
Although studies on da'wah have been widely conducted, research that specifically integrates geographical, demographic, social, cultural, and religious aspects within a single mapping framework remains limited, especially in Tigo Lurah Subdistrict, Solok Regency. This study aims to describe and analyze the da'wah map as a basis for formulating more effective and contextual da'wah strategies. This study employed a qualitative approach with a descriptive design. The informants consisted of religious leaders, mosque administrators, government officials, and community members who were selected through purposive sampling. Data were collected through observation, interviews, and documentation, then analyzed using an interactive model that includes data reduction, data presentation, and conclusion drawing. The results showed that the implementation of da'wah had not yet been optimal, as indicated by limited geographical access, low community participation, especially among the younger generation, the dominance of lecture-based methods that were less varied, and the uneven distribution of da'i. Nevertheless, the community has social potential in the form of togetherness values and religious traditions that can be further developed. These findings contribute to strengthening a social mapping-based approach to da'wah and provide a practical foundation for formulating more contextual da'wah strategies. The conclusion of this study emphasizes the importance of developing more varied da'wah methods and increasing community participation to support the effectiveness of da'wah in the area.